BAHASA DAN GENDER - Praseto Adi Wisnu Wibowo (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2012)
We can see the fact that the style and the characteristic choice of a conversation is influenced byÂ gender. Gender is one of the basic factors that influences and forms social construct and several conversations about gender. Gender is not related to the characteristics possessed by someone, but it exists and is possesed by every person. Different gender willÂ influence the form of utterance. Keywords: gender, language, utterances